Association of Kidney Disease With Abnormal Cardiac Structure and Function Among Ugandans With HIV Infection. (1st January 2021) - Peters, Matthew; Margevicius, Seunghee; Kityo, Cissy; Mirembe, Grace; Buggey, Jonathan; Brinza, Ellen; Schluchter, Mark; Yun, Chun-Ho; Hung, Chung-Lieh; McComsey, Grace A.; Longenecker, Chris T.
Abstract : Background: People with HIV (PWH) are at an increased risk of both heart and kidney disease, but the relationship between kidney disease and cardiac structure and function in this population has not been well studied. In particular, whether the relationship between kidney disease and cardiac structure and function is stronger for PWH compared with uninfected controls is unknown. Methods: One hundred PWH on antiretroviral therapy were compared with 100 age-matched and sex-matched controls without HIV in Uganda. Multivariable regression models were used to examine associations between creatinine-based and cystatin C-based estimated glomerular filtration rate (eGFR), albumin–creatinine ratio, and echocardiographic measures of cardiac structure and function. Results: PWH had lower eGFRcr (β −7.486, 95% confidence interval: −13.868 to −1.104, P = 0.022) and a higher rate of albumin–creatinine ratio ≥30 (odds ratio 2.146, 95% confidence interval: 1.027 to 4.484, P = 0.042) after adjustment for traditional risk factors. eGFR was inversely associated with both left ventricular mass index and diastolic dysfunction in adjusted models but not with systolic function. Albuminuria was associated with more diastolic dysfunction among PWH but not controls ( P for interaction = 0.046). The association of HIV with a higher left ventricular mass index ( P = 0.005) was not substantially affected by adjusting for eGFRcr . Conclusion: Among Ugandans, eGFR is associated with elevated LV mass and diastolic dysfunction. The association between albuminuria and diastolic dysfunction is particularly strong for PWH.